2021
DOI: 10.3390/brainsci11010082
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Synaptic Plasticity by Vibratory Training in Young and Old Mice

Abstract: In the past 40 years, scientific research has shown how Whole Body Vibration concept represents a strong stimulus for the whole organism. Low (<30 Hz), medium (30–80 Hz), and high (>80 Hz) frequency vibrations can have both positive and negative effects, depending on the oscillation type and duration of exposure to which the body is subjected. However, very little is known about the effects of vibratory training on the brain. In this regard, we verified whether three vibratory training protocols, differi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 37 publications
4
26
0
Order By: Relevance
“…In our previous work, we reported that exposure to an appropriate WBV protocol improves learning and memory processes in old mice (Cariati et al, 2021). These brain functions are particularly susceptible to the aging process.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…In our previous work, we reported that exposure to an appropriate WBV protocol improves learning and memory processes in old mice (Cariati et al, 2021). These brain functions are particularly susceptible to the aging process.…”
Section: Discussionmentioning
confidence: 94%
“…Vibration training was conducted using three protocols (A, B, and C), which differ in terms of vibration frequency and exposure time to vibration (Cariati et al, 2021). The A and B protocols consisted of five series (consecutive number of repetitions) of 3 min each, interspersed with 1 min of recovery.…”
Section: Training Protocolsmentioning
confidence: 99%
See 3 more Smart Citations